To Study the Effects of Simvastatin on Lipid Profile in Obese Patients - MUNIZA QAYYUM, ABDUL HAMEED KHAN, LUBNA AMER, RUKHSHAN KHURSHID (Journal of Fatima Jinnah Medical University, 2018)
Simvastatin is a competitive inhibitor of HMG-CoA (3Hydroxy 3Methyl Glutaryl Coenzyme A) reductase. 20 male and 20 female obese patients were selected. The obese patients were re-examined three times i.e. before giving the simvastatin, then after 6 and 12 weeks. The patients were advised to take fat free diet and a morning walk. Serum Cholesterol, serum Triglycerides and serum Lipoprotiens (HDL, LDL) was carried out by Standard kit methods (Merck). This study shows that with use of Simvastatin serum cholesterol, serum triglycerides, and serum LDL-Cholesterol was reduced significantly and serum HDL-Cholesterol increased significantly in both sexes and causes weight reduction which may be due to low calorie diet and physical exercise. It is therefore concluded that Simvastatin shows significant lipid lowering effects and also reduced the body weight, if patients used calorie restricted diet with some morning walk.